The benefit of wireless network among OM students in UiTM Perak / Atikah Ahmad, Farahwanida Nor Azhar and Haslinda Mohd Hashim - Ahmad, Atikah; Nor Azhar, Farahwanida; Mohd Hashim, Haslinda (2009)
Wireless Internet technology is gaining a foothold on more and more campuses, yet few studies have investigated how wireless Internet supports and enhance student work performance. This study seeks to identify the factors that influence the wireless usage in UiTM Perak for OM students. Other objective of this study is to determine how frequent the OM students use the wireless Internet in campus and the last objective is to identify the benefits of using wireless Internet in UiTM Perak. The study was conducted at UiTM Perak and the questionnaire was designed and administered personally for OM students. The research discovers that wireless Internet really gives benefit to them in terms of ease of access to the network and online information and also ease of downloading files. However, from the survey and interview that were conducted, many students expressed their expectation to have more wireless coverage across campus and to solve this problem; more buildings and classroom must be equipped with wireless connectivity.